Optimization of DNA Extraction and PCR Conditions for Genetic Diversity Study in Artemisia Herba- Alba from Algeria - Benchohra Maghni; Youcef Bougoutaia; Khadidja Abderrabi; Ahmed Adda; Othmane Merah (Scientific Journal of Genetics and Gene Therapy - Peertechz Publications, 2016)
Background: Artemisia herba alba is an aromatic species very rich in secondary metabolites that can be used in traditional medicine. The context and purpose of the study: This species suffers from the degradation of its natural habitat. The creation of collections containing diverse ecotypes is important for its preservation. This species contains essential oils which limit the extraction of DNA. The objective of this study is to optimize the DNA extraction and PCR conditions. The method will be used to evaluate the genetic diversity of Artemisia herba alba in the highlands of Western Algeria as a starting point. Results and main findings: The use of different reagents and the modification of the incubation time allow obtaining white and clear DNA. Moreover, the modification of temperature and duration of hybridization results in clearer ISSR profiles. The use of the genetic markers for the analysis of genetic material ISSR, carried out on 12 individuals, indicates that A. herba alba is characterized by a broad genetic polymorphism. Conclusions: This study permits the optimization of protocol of DNA extraction and amplification by PCR for A. herba alba. Large variability was found between the studied individuals for A. herbaalba. The developed markers could be used for screening a large collection of individuals. Brief summary: Artemisia herba alba is a popular medicine plant in North Africa. This plant shows a degradation of its natural habitat. It is necessary to constitute a collection in order to reintroduce it in the highlands of North Africa. For this purpose the genetic characterization is obviously important. Nevertheless, no information is available on this species. Moreover, its essential oils limit markedly the DNA extraction. This study aimed the optimization of DNA extraction and PCR conditions. The results showed, by using different reagents and both time and temperature of incubation, a clearer DNA and ISSR markers profiles. This study also revealed a large variability within A. herba alba which could help investigation on a large collection of individuals and therefore select the most efficient ecotypes for re-introduction this species in highlands of Algeria.